Narrating to Survive: Ethics and Aesthetics in Githa Hariharan’s When Dreams Travel - Sankaran, National University of Singapore, Chitra (Asiatic: IIUM Journal of English Language and Literature, 2008)
Githa Hariharan, winner of the Commonwealth Writers Prize for Fiction (1993), explores significant issues with regard to narrativity in her novel,Â When Dreams Travel. The narrator weaves around Scheherazade â€“ or Shahrzad of theÂ Arabian NightsÂ â€“ a vibrant and inventive story about a perennially played out game: the quest for love and power. Between the Sultan who wants a virgin every night and his brother who has felt the bitter taste of betrayed love exist two women, two ambitious brides, who are the sisters Shahrzad and Dunyazad, aspiring to be heroines or martyrs. The tale that unravels with all the tour-de-force of a modern myth explores a range of issues â€“ the fallibility of narrative and the crisis involved in the act of narrativity itself. It engages with questions of ethics and the importance of aesthetics to ethics. Â Â In my paper I shall be engaging with all of these above issues trying to explore the edge of meaning in extreme acts of narrativity such as in Shahrzadâ€™s case and how these impact on questions of ethics and aesthetics in narratives.